Updating and characterizing neuroanatomical markers in high-risk subjects, recently diagnosed and chronic patients with schizophrenia: A revised coordinate-based meta-analysis. (April 2021) - Liloia, Donato; Brasso, Claudio; Cauda, Franco; Mancuso, Lorenzo; Nani, Andrea; Manuello, Jordi; Costa, Tommaso; Duca, Sergio; Rocca, Paola
Graphical abstract: Highlights: We reviewed and meta-analyzed 113 VBM studies about different stages of SZ. The first CBMA on SZ stages employing ALE revised algorithm, behavioral analysis and functional network decomposition. Common/distinctive gray matter changes were found for clinical high-risk, first-episode and chronic SZ. The ACC, AI, amygdala, PHG and thalamus appear to play a role in the progression of SZ. Alteration maps can be used as priors for future neuroimaging investigations about SZ. Abstract: Characterizing neuroanatomical markers of different stages of schizophrenia (SZ) to assess pathophysiological models of how the disorder develops is an important target for the clinical practice. We performed a meta-analysis of voxel-based morphometry studies of genetic and clinical high-risk subjects (g-/c-HR), recently diagnosed (RDSZ) and chronic SZ patients (ChSZ). We quantified gray matter (GM) changes associated with these four conditions and compared them with contrast and conjunctional data. We performed the behavioral analysis and networks decomposition of alterations to obtain their functional characterization. Results reveal a cortical-subcortical, left-to-right homotopic progression of GM loss. The right anterior cingulate is the only altered region found altered among c-HR, RDSZ and ChSZ. Contrast analyses show left-lateralized insular, amygdalar and parahippocampal GM reduction in RDSZ, which appears bilateral in ChSZ. Functional decomposition shows involvement of the salience network, with an enlargement of the sensorimotor network in RDSZ and the thalamus-basal nuclei network in ChSZ. These findings support the current neuroprogressive models of SZ and integrate this deterioration with the clinical evolution of the disease.